CORE VALUE BERAKHLAK MENJADI NILAI DASAR ETIKA DAN BUDAYA KERJA APARATUR SIPIL NEGARA SEBAGAI PELAYANAN PUBLIK - Sudung Simatupang; Kevin Indajang; Ernest Grace; Vivi Candra; Dermawan Perangin-Angin (Bajang Institute, 2025)
The State Civil Apparatus (ASN) today has a basic value of work ethics and culture, this is known as CoreValue Berahlak, and is used as a guideline in the process of carrying out its duties and functions as a public servant. This research uses a qualitative method, which contains a description of the State Civil Apparatus (ASN) as a public servant, and is always guided by the provisions provided by the government, which in this case are guidelines for the CoreValue Berahlak. By applying BERAKHLAK values (Service-Oriented, Accountable, Competent, Harmonious, Loyal, Adaptive, and Collaborative), ASN can work more professionally and quality in providing services to the community. BERAKHLAK Core Values are not just a slogan, but as the main principle that must be applied by every ASN to create quality, professional, and community-oriented public services